The listening bilingual speech perception, comprehension, and bilingualism - Grosjean, François; Byers-Heinlein, Krista (Wiley-Blackwell, 2018)
"A book such as this one on a specialized topic - the perception and comprehension of speech by bilinguals - needs to begin with a brief description of bilingual adults and children. Those who are interested in the topic may be familiar with speech perception and comprehension issues but might not know as much about bilingualism. They might also have a few misconceptions about what it means to be bilingual, both for the adult and the child. Many preconceived ideas surround bilingualism, such as that bilinguals have equal and perfect knowledge of their two or more languages, that they all acquired their languages as children, that they are competent translators, or that they do not have an accent in any of their languages. As concerns children, it was long believed that bilingualism would delay their language acquisition and create confusion, or that they would invariably mix their languages, or even that being bilingual would have negative effects on their development. The first aim of this chapter is to give a brief overview of bilingual adults and children and to lay the foundations for a better understanding of issues that relate to their perception and comprehension of speech"-- Provided by publ